Neuroglial transmitophagy and Parkinson's disease. Issue 11 (16th May 2020) - Morales, Ingrid; Sanchez, Alberto; Puertas‐Avendaño, Ricardo; Rodriguez‐Sabate, Clara; Perez‐Barreto, Adrian; Rodriguez, Manuel
Abstract: Mitophagy is essential for the health of dopaminergic neurons because mitochondrial damage is a keystone of Parkinson's disease. The aim of the present work was to study the degradation of mitochondria in the degenerating dopaminergic synapse. Adult Sprague–Dawley rats and YFP‐Mito‐DAn mice with fluorescent mitochondria in dopaminergic neurons were injected in the lateral ventricles with 6‐hydroxydopamine, a toxic that inhibits the mitochondrial chain of dopaminergic neurons and blockades the axonal transport. Dopaminergic terminals closest to the lateral ventricle showed an axonal fragmentation and an accumulation of damaged mitochondria in 2–9 μ saccular structures (spheroids). Damaged mitochondria accumulated in spheroids initiated (showing high Pink1, parkin, ubiquitin, p‐S65‐Ubi, AMBRA1, and BCL2L13 immunoreactivity and developing autophagosomes) but did not complete (mitochondria were not polyubiquitinated, autophagosomes had no STX17, and no lysosomes were found in spheroids) the mitophagy process. Then, spheroids were penetrated by astrocytic processes and DAergic mitochondria were transferred to astrocytes where they were polyubiquitinated (UbiK63+) and linked to mature autophagosomes (STX17+) which became autophagolysosomes (Lamp1/Lamp2 which co‐localized with LC3). Present data provide evidence that the mitophagy of degenerating dopaminergic terminals starts in the dopaminergic spheroids and finishes in the surrounding astrocytes ( spheroid‐mediated transmitophagy ). The neuron‐astrocyte transmitophagy could be critical for preventing the release of damaged mitochondria to the extracellular medium and the neuro‐inflammatory activity which characterizes Parkinson's disease. Main Points: Damaged mitochondria of degenerating dopaminergic synapsis are transferred to striatal astrocytes for their degradation (transmitophagy). A transmitophagy failure could be critical in Parkinson's disease.